(untitled) (Research, Society and Development, 2020)
This work is based on the concern with the increasing rates of emotional problems that have been affecting the professional nurse, and which are especially exacerbated during the pandemic of COVID-19. In the meantime, the objective of this article is to conduct a theoretical reflection on the emotional suffering of nurses in the hospital context in the face of the COVID-19 pandemic. It is a narrative review of the literature developed by searching for publications obtained from the databases: PubMed, BVS, LILACS and SciELO. The keywords emotional distress, COVID-19, nurse, pandemics, emotional distress and mental health were used. At the end, 33 publications were selected to compose the study. Through the analysis of the studies, it was possible to show that nurses in times of COVID-19 have been developing several problems in their mental health, such as anxiety, stress, and even depression. This is due to frustration, physical and mental exhaustion, feelings of helplessness and professional insecurity. It is concluded, therefore, that it is essential to take greater care with the psycho-emotional health of nurses, based on investments and actions that contemplate better working environments and conditions.